Knowledge on rabies transmission, immunisation and wound management among medical undergraduate students at a medical institute in North India - Chandrappa, Gurutheja H.; Kumari, Reema (International Journal Of Community Medicine And Public Health, 2026)
Background: Medical undergraduates, as future frontline healthcare providers, are instrumental in early detection, risk stratification, and management of rabies exposures. Evaluating their knowledge particularly regarding rabies transmission routes, WHO exposure categories, wound care, and post-exposure prophylaxis is vital for guiding educational interventions and enhancing clinical competencies in rabies prevention and control at both institutional and public health levels. Methods: A cross-sectional study was conducted among 240 medical undergraduate students from King George’s Medical University in Lucknow from May 2025 to July 2025. A pre-tested, semi-structured, self-administered questionnaire was sent as a Google form to all the participants via WhatsApp messaging app. All the participants responded to the questionnaire. Hence, the final analysis comprised of these 240 respondents. Results: While medical undergraduates have strong knowledge of rabies causation, reservoirs, wound washing, and avoidance of harmful practices, there are misconceptions in understanding of categorizing the exposure, risk-based management, and intradermal vaccination protocols. Conclusions: The findings suggest the importance of enhancing clinical scenario-based teaching and incorporating updated guidelines into medical curriculum to bridge these knowledge gaps.